Electrically tunable optical properties of few-layer black arsenic phosphorus. (28th September 2018) - Yu, Li; Zhu, Zhen; Gao, Anyuan; Wang, Junzhuan; Miao, Feng; Shi, Yi; Wang, Xiaomu
Abstract: Black arsenic phosphorus (b-AsP) is a promising two-dimensional material for various optoelectronic applications, bridging the wavelength gap between two-dimensional molybdenum disulfide and graphene. In particular, it has intriguing potential in photodetectors and great advantages in the mid-infrared field. However, its optoelectronic modulation has yet to be elucidated, which requires a fundamental understanding of its field-effect optical modulation. Here, we report the measurements of the lower-energy infrared anisotropic optical response of thin b-AsP under different electrical gating. We reveal that in addition to band edge absorption, amplitude modulation of sub-band absorption up to ten percent is also obtained in reflection extinction. These in-gap absorptions are attributed to spin–orbital coupling and free carrier absorption. Our results suggest the important potential for use of b-AsP in mid-infrared optoelectronic modulator applications.